Synthesis, Spectroscopic, Thermal and X-Ray Structure of Aminoguanidinium and Hydrazinium Uranyl Trichloroacetates - Ahamed Hussain, T.M.; Sivasankar, B.N. (Asian Journal of Chemistry, 2019)
New aminoguanidinium and hydrazinium uranyl complexes of trichloroacetate with formulae H2(HAgun)2[UO2(Cl3COO)5](NO3) (1) and (N2H5)[UO2(Cl3COO)3] (2) where HAgun is aminoguanidinium cation have been prepared in aqueous media and charaterized by analytical, spectral, thermal and X-ray crystallographic studies. The electronic spectra of the complexes confirm the presence of uranyl cation in the molecules. The infrared spectra of the complexes show the N-N stretching frequency of aminoguanidinium in the range of 1100 cm-1 and for hydrazinium in the range of 970 cm-1 conforming their ionic nature. The simultaneous TG-DTA of both the complexes show two step degradation to yield U3O8 as the final residue which was confirmed by X-ray powder diffraction. The structural morphology of U3O8 has been studied by SEM technique. The crystal structure of compound 1 reveals seven coordination around uranium with pentagonal bipyramidal geometry. Aminoguanidinium cations and nitrate anion are present outside the coordination sphere as charge compensating species. However, for hydrazine complex hexagonal bipyramidal geometry has been assigned on the basis of analytical and spectral studies.